Club convergence in the eurozone: A look at inequality dynamics - Vale, S. (Economics Letters, 2024)
This paper examines the convergence of eurozone countries’ inequality indicators between 1995 and 2020. The Phillips and Sul (2007, 2009) methodology is used to determine the existence of convergence clubs. Our findings show that eurozone countries follow a similar trajectory in terms of the income of the richest 1% of the population and are divided into two clusters based on other inequality indicators.